Isospin sum rules for bottom-baryon weak decays - Wei-Chen Fu; Si-Jia Wen; Di Wang (European Physical Journal C: Particles and Fields)
Abstract Isospin symmetry, as the most precise flavor symmetry, can be used to extract information about hadronic dynamics. The effective Hamiltonian operators of bottom quark weak decays are zero under a series of isospin lowering operators $$I_-^n$$ I - n , which permits us to generate isospin sum rules without the Wigner–Eckart invariants. In this work, we derive hundreds of isospin sum rules for the two- and three-body non-leptonic decays of bottom baryons. They provide hints for new decay modes and the isospin partners of pentaquark states.